# 6

)

JJC/05/P1/Q1
1
in ascending powers of x up to and including the term in
Expand 3
8+ x
x2 .

[3]

MJC/05/P2/Q5
7)

8)

1 + 6x − 6x2
(x 2 + 1)(2 x − 1) .
Hence, or otherwise, obtain the expansion of f ( x ) in ascending powers of x
up to and including the term in x3.
State the range of values of x for which the expansion is valid.
Express f ( x ) as partial fractions, where f ( x ) =

[4]
[4]
[1]

NYJC/05/P1/Q1
Find the first four terms of (1 − x) −2 , stating the range of x for which this
expansion is valid.

3r
By choosing a suitable value of x, find ∑ r −1 .
[5]
r =1 2
RJC/05/P1/Q5

9)

Expand (4 + y )2 in ascending powers of y up to and including the term in
1

y 3 . Simplify the coefficients.

[3]

(

In the expansion of 4 + 8 x + kx

)

1
2 2

, where k is a constant, the coefficient

of x is zero. By writing 8 x + kx as y, find the value of k .
3

10)

2

TJC/05/P1/Q7
3 + 2 x − 11x 2
Ax + B
C
Express
in the form
+
where A, B and C are
2
2
2 1 + x (1 − 2 x )
1+ x
1 − 2x
constants.
3 + 2 x − 11x 2
Hence or otherwise, expand
in ascending powers of x up to
2 1 + x 2 (1 − 2 x )
and including the term in x2. State the values of x for which the expansion is
valid.

(

[2]

)

(

[3]

)

TPJC/05/P1/Q1
11) Find the binomial expansion of 1 + 2 x up to and including the term in x3,
simplifying the coefficient. State the values of x for which this expansion is
valid.

[4]

[4]

VJC/05/P1/Q8
12) i)
x2 + x + 7
Express
in partial fractions.
(1 − x )(x + 2)2
ii)

[4]

−2

x

Show that the expansion of 1 +  in ascending powers of x up to
 2
3 

and including the x 2 term is 1 − x + x 2  .
4 

iii) Given that (1 − x )−1 = 1 + x + x 2 + K , find the expansion of
x2 + x + 7
in ascending powers of x up to and including the x 2
2
(1 − x )(x + 2)
term.

[2]

[2]

Possible solutions
1)

B

π

π

6

+x

4
C
A
Using sine rule
BC
AC
AB
=
=
π
π
 sin C
sin
sin  + x 
4
6

BC
=
AC
=

=

=

sin

π

4

π
sin  + x 

6
1

π
 π

2 sin cos x + cos sin x 
6
 6

1
1

3
2  cos x +
sin x 
2
2

2
 x

1 −
+ L + 3 ( x + L)
2

2

x2
= 2 1 + 3 x −
+ L
2

−1

 

x2
= 2 1 +  3 x −
+ L
2

 

−1

1
2
 

 (− 1)(− 1 − 1) 

x2
x2
 3 x −
= 2 1 −  3 x −
+ L +
+ L + L
2
2!
2
 


2
 
x2  
x2  
≈ 2 1 −  3 x −  +  3 x −  
2  
2 
 

( )

x2
≈ 2 1 − 3 x +
+ 3x 2 
2

7 

≈ 2 1 − 3 x + x 2 
2 

2)

4x3 − 2x2 + 1
4x3 − 2x2 + 1
2x2 − 2x + 3
=
=
2
+
(x − 1)(2 x 2 + 1)
( x − 1)(2 x 2 + 1) 2 x 3 − 2 x 2 + x − 1
2x2 − 2x + 3
Q
Rx + S
=
+ 2
2
(x − 1) 2 x + 1 (x − 1) 2 x + 1

(

)

(

)

2 x − 2 x + 3 = Q 2 x 2 + 1 + (Rx + S )( x − 1)
2 − 2 + 3 = Q(2 + 1)
When x = 1 ,
Q =1
0 − 0 + 3 = 1(0 + 1) + (S )(− 1)
When x = 0 ,
S = −2
8 − 4 + 3 = 1(8 + 1) + (2 R − 2 )(2 − 1)
When x = 0 ,
R=0
3
4x − 2x2 + 1
1
2
= 2+

Therefore
. P = 2, Q = 1, R = 0, S = −2
2
2
(x − 1) 2 x + 1
( x − 1)(2 x + 1)
2

(

)

4x3 − 2x2 + 1
1
2
= 2+

2
2
(x − 1) 2 x + 1
( x − 1)(2 x + 1)

(

)

(
)
= 2 − (1 − x ) − 2(1 + 2 x )
= 2 + ( x − 1) − 2 1 + 2 x 2
−1

−1

−1

2 −1

(− 1)(− 1 − 1) (− x )2 + 

1
1 + (− 1)(− x ) +

2!
= 2−

 (− 1)(− 1 − 1)(− 1 − 2 ) (− x )3 + L



3!

[

]

( )

− 2 1 + (− 1) 2 x 2 + L
1

[

] (

)

= 2 − 1 + x + x + x + L − 2 1 − 2x 2 + L
2

3

= −1 − x + 3 x − x + L
The series is valid for x < 1 and 2 x 2 < 1 .
2

2

3

Therefore the series is valid for x <

1
.
2

3)

1
x +1

= ( x + 1)(1 − 2 x ) 2
1 − 2x

 1  1 
 −  − − 1

1
1 +  − (− 2 x ) +  2  2  (− 2 x )2 + 
2
2!

= (1 + x ) 

  − 1  − 1 − 1 − 1 − 2 

  2  2  2

 (− 2 x )3 + L


3!
3
5

= (1 + x )1 + x + x 2 + x 3 + L
2
2

3
5
1 + x + x2 + x3 + L
2
2
=
3
+ x + x2 + x3 + L
2
5
= 1 + 2x + x 2 + 4x3 + L
2
1
The series is valid for 2 x < 1 ⇒ x <
2
1
12
+1
1
x +1
12
11
4
When x = ,
= 11
= 11 = ×
=
11 1 − 2 x
9 11 3
11
1
1 − 2 
11
 11 
2

3

 1  5 1 
1
= 1 + 2  +   + 4  + L
11
 11  2  11 
 11 
 3209 
11 ≈ 4 ÷ 
 2662 
10648

3209
≈ 3.32

4

4)

(

)

(

)

x3 − x −1
x3 − x −1
− x2
− x2
=
=
1
+
=
1
+
x 2 − 1 ( x + 1) x 3 + x 2 − x − 1
x3 + x 2 − x −1
x 2 − 1 ( x + 1)
− x2
− x2
B
C
D
=
=
+
+
2
2
x − 1 x + 1 (x + 1)2
x − 1 (x + 1) ( x − 1)(x + 1)

i) f ( x ) =

(

(

)

(

)

)

− x 2 = B( x + 1) + C ( x − 1)( x + 1) + D( x − 1)
1
2
When x = 1 , − 1 = B(2 ) ⇒ B = −
4
1
When x = −1 , − 1 = D(− 1 − 1) ⇒ B =
2
1 2
1
3
When x = 0 , 0 = (1) + C (− 1) + (− 1) ⇒ C = −
2
2
4
3
x − x −1
1
3
1
f (x ) = 2
= 1−

+
4(x − 1) 4(x + 1) 2(x + 1)2
x − 1 (x + 1)
ii)
1
3
1
f (x ) = 1 −

+
4(x − 1) 4(x + 1) 2(x + 1)2
1
3
1
−1
−1
−2
= 1 + (1 − x ) − (1 + x ) + (1 + x )
4
4
2
1
3
= 1 + 1 + x + x 2 + x3 + L − 1 − x + x 2 − x3 + L
4
4
1
+ 1 + −2 x + +3 x 2 − 4 x 3 + L
2
1
1 1
1 2
1 3
+
x
x
x
+L
4 4
4
4
3
3
3
= 3

+ x − x 2 + x3 + L
4
4
4
4
1
3 2
+
−x
x
− 2x3 + L
2
2
2
3
= 1+ x − x +L
The series is valid for x < 1 .
2

(

)

(

) (

[

x 2005 of f ( x ) is the 2006th term of

)

]

1
(1 − x )−1 + 2006th term of − 3 (1 + x )−1 + 2006th
4
4

1
(1 + x )− 2
2
1 2005 3
1
2006 +1 2005
2006 +1
(2006)x 2005 =  1 + 3 − 1003  x 2005 = −1002 x 2005
x
− (− 1)
x
+ (− 1)
4
4
2
4 4

term of

Therefore coefficient of x 2005 is -1002.

5)

(2 − x )

−2

−2

 x
= 2 1 − 
 2
1
2

 x  (− 2 )(− 2 − 1)  x  
(
)
1
+

2

+

 +

2!
1
 2
 2 
=

4  (− 2 )(− 2 − 1)(− 2 − 2 )  x 3

−  +L
3!


 2
−2

1
3
1

1 + x + x 2 + x 3 + L

4
4
2

1 3
1
= + x 2 + x3 + L
4 16
8
x
The series is valid for
<1⇒ x < 2 .
2
=

The term of x r is the (r + 1) term in the series.
th

(r + 1)

th

1  (− 2 )(− 2 − 1)(− 2 − 2 )L (− 2 − r + 1)  x 
term = 
 − 2 
4
r!
1  (− 1) (2 )(3)(4 )L(r )(r + 1) (− 1) r

 r x
4
r!
 2
r

=
=
6)

1
3

8+ x

(r + 1)
2r +2

= (8 + x )

1
3

r

1
3

 x
= 8 1 + 
 8

1
3

 1  1 

 −  − − 1
2
 1  x   3  3   x 

= 2 1 +  −   +
  + L
  3  8 
2
8

1
1 2
= 2− x−
x +L
48
576
x
The expansion is valid for
<1⇒ x < 8
8

r

7)

Let

1 + 6x − 6x2
Ax + B
C
= 2
+
2
x + 1 (2 x − 1) x + 1 2 x − 1

(

)

(

)

1 + 6 x − 6 x 2 = ( Ax + B )(2 x − 1) + C x 2 + 1
1 1
1 
1 1 + 6  − 6  = +C  + 1
When x = ,
2 4
4 
2
C=2
1 = −B + 2
When x = 0 ,
B =1
1 + 6 − 6 = ( A + 1)(2 − 1) + 2(1 + 1)
When x = 1 ,
A = −4
1 + 6x − 6x2
1 − 4x
2
f (x ) = 2
= 2
+
x + 1 (2 x − 1) x + 1 2 x − 1

(

f (x ) =

)

1 − 4x
2
+
2
x + 1 2x − 1

( ) − 2(1 − 2 x )
= (1 − 4 x )[1 − x + L] − 2[1 + 2 x + (2 x ) + (2 x )
= (1 − 4 x ) 1 + x 2

−1

2

−1

2

3

]

+L

= 1 − x 2 − 4 x + 4 x 3 + L − 2 − 4 x − 8 x 2 − 16 x 3 + L
= −1 − 4 x − 9 x 2 − 12 x 3 + L
The series is valid for x 2 < 1 and 2 x < 1 ⇒ x <
8)

1
2

(1 − x )−2 = 1 + 2 x + 3x 2 + 4 x 3 + L
The expansion is valid for x < 1 .

3r
r
=
3

r −1
r −1
r =1 2
r =1 2
2
3

1
1 1
1
= 31 + 2  + 3  + 4  + L, subst x = into expansion
2
2 2
2



 1
= 31 − 
 2
= 12

−2

9)

1

(4 + y )

1
2

y 2

= 21 + 
 4

 1  1 
 1  1  1

  1  y   2  2 − 1  y  2  2  2 − 1 2 − 2   y 3

 


= 2 1 +    +  
  +
  + L
2!
3!
  2  4 
4
4



1 2
1
 1

= 2 1 + y −
y +
y 3 + L
128
1024
 8

1
1 2
1 3
= 2+ y−
y +
y +L
4
64
512
y
The expansion is valid for
<1⇒ y < 4
4
Let y = 8 x + kx 2

(4 + 8x + kx ) = (4 + y )
1
2 2

1
2

1
1 2
1 3
y−
y +
y +L
4
64
512
2
3
1
1
1
= 2 + 8 x + kx 2 −
8 x + kx 2 +
8 x + kx 2 + L
4
64
512
1
1
=L−
64 x 2 + 16kx 3 + k 2 x 4 +
512 x 3 + L + L
64
512
k
= L − x3 + x3 + L
4

= 2+

(

)

(

k
+1 = 0
4
k =4

(

)

)

(

(

)

)

10)

3 + 2 x − 11x 2
Ax + B
C
=
+
2
2
2 1 + x (1 − 2 x ) 1 + x
1 − 2x
1
3 + 2 x − 11x 2 = ( Ax + B )(1 − 2 x ) + C 1 + x 2
2
1
1
 1 
 1
3 + 2  − 11  = +C 1 + 

1 2
2
 4 
 4
When x = , 
2
1
C=
2
3
1
= B(1) + (1)
When x = 0 , 2
2
B =1
1
(3 + 2 − 11) = ( A + 1)(1 − 2) + 1 (1 + 1)
When x = 1 , 2
2
A=3

(
(

)

)

(

)

3 + 2 x − 11x 2
3x + 1
1
=
+
2
2
2 1 + x (1 − 2 x ) 1 + x
2(1 − 2 x )

(

)

3 + 2 x − 11x 2
3x + 1
1
=
+
2
2
2 1 + x (1 − 2 x ) 1 + x
2(1 − 2 x )

(

)

(

= (3 x + 1) 1 + x 2

)

1
(1 − 2 x )−1
2
1
= (3 x + 1) 1 − x 2 + L + 1 + 2 x + 4 x 2 + L
2
1
= 3x + 1 − x 2 + L + + x + 2 x 2 + L
2
3
= + 4x + x2 + L
2
1
The expansion is valid for x < 1 and 2x < 1 ⇒ x
2

(

−1

+

)

(

)

2

11)

+

=( +

)2
1

 
= +  (
 
= + −

 

  − 
(
) +  
2

+

3

+L

)2

 


  −  − 

(
+  

)3 + L

12)

i) Let

x2 + x + 7
A
B
C
=
+
+
2
(1 − x )(x + 2 ) 1 − x x + 2 (x + 2)2

x 2 + x + 7 = A( x + 2 ) + B(1 − x )( x + 2 ) + C (1 − x )
2

When x = 1 , 1 + 1 + 7 = A(1 + 2 ) ⇒ A = 1
When x = −2 , 4 − 2 + 7 = C (1 + 2) ⇒ C = 3
When x = 0 , 7 = 4 + B(1)(2) + 3 ⇒ B = 0
2

x2 + x + 7
1
3
=
+
2
(1 − x )(x + 2) 1 − x (x + 2)2
ii)
−2
2
 x
 x  (− 2 )(− 2 − 1)  x 
1 +  = 1 + (− 2 )  +
  +L
2!
 2
 2
2
3
= 1 − x + x2 + L
4
x
The expansion is valid for
<1⇒ x < 2
2
iii)
x2 + x + 7
1
3
=
+
2
(1 − x )(x + 2) 1 − x (x + 2 )2
= (1 − x ) + 3( x + 2 )
−1

−2
−2

3 x
= 1 + x + x 2 + K + 1 + 
4 2
3
3

= 1 + x + x 2 + K + 1 − x + x 2 + L
4
4

7 1
25 2
= + x+
x +L
4 4
16
x
The expansion is valid for x < 1 and < 1 ⇒ x < 1
2